THU0465 Genetic Control of the Immune Response to Histone Derived Citrullinated Peptides in Rheumatoid Arthritis Patients. (10th June 2014) - Pratesi, F.; Petit-Teixeira, E.; Ancillotti, D.; Panza, F.; Cornelis, F.; Migliorini, P.
Abstract : Background: Rheumatoid arthritis (RA) sera contain antibodies specific for deiminated peptide/proteins (ACPA) directed against endogenous (filaggrin, fibrin, vimentin, collagen, enolase) or exogenous antigens. Recently ACPA reacting with citrullinated peptides derived from histone H4 have been detected. It is widely accepted that HLA-DRB1 alleles encoding the shared epitope sequences are associated with the production of ACPAs. However, the genetic background underlying the production of single ACPA specificities has not been thoroughly investigated. Objectives: To analyze the reactivity to two different histone H4 derived citrullinated peptides (HCP1 = citrullinated H414–34 and HCP2 = citrullinated H431–50 ) and to study their association with genetic variants within HLA-DRB1 SE alleles in a RA population. Methods: One hundred and seventy-two French RA patients were characterized in terms of HLA-DRB1 genotype, anti VCP-A and anti-VCP-B antibodies. HLA-DRB1 typing was performed using the polymerase chain reaction-sequence specific primer (SSP) method, and SE alleles were classified into four SE+ groups (S1, S2, S3P, S3D) and one SE- group (X) according to the new classification of HLA-DRB1 alleles, reshaping the shared epitope (SE) hypothesis [1]. Anti-HCPs antibodies were assessed by home made ELISA on HCP1 and HCP2 coated plates. Results: Setting the threshold value at the 98° percentile of the normal population, anti-HCP1 antibodies are present in 46% and anti-HCP2 antibodies in 62% of RA patients. Anti-HCP1 antibodies are not associated with HLA-SE alleles. On the contrary, anti-HCP2 antibodies are associated with HLA-DRB1 *0102 (p=0.04), *0401 (p=0.03), *0404 (p=0.01). Subgrouping the SE alleles according to the new classification, the presence of anti-HCP2 antibodies is associated with S2 allele (p<0.05). Conclusions: Using two histone H4 derived citrullinated peptides as probes, we showed genetic heterogeneity in the control of the immune response to single components of the ACPA family and to different portion of the same molecule. These data underline the need to type RA patients for different ACPA specificities, that may contribute to the identification of different subsets of patients. References: du Montcel ST et al. Arthritis Rheum. 2005, 52(4): 1063-8 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5450